Peak Growth Hormone-Releasing Hormone-Arginine-Stimulated Growth Hormone Is Inversely Associated with Intramyocellular and Intrahepatic Lipid Content in Premenopausal Women with Obesity - Bredella, Miriam A. (The Endocrine Society, 2009)
Context: Visceral adiposity is a strong determinant of GH secretion, and low endogenous GH secretion is associated with increased insulin resistance, a key component of the metabolic syndrome. Increased fat accumulation in skeletal muscle and liver may play an etiological role in the development of insulin resistance and other complications of the metabolic syndrome. Little is known about the role of decreased endogenous GH secretion in the pathogenesis of insulin resistance in obesity. Objective: To investigate the relationship between intramyocellular lipids (IMCL), intrahepatic lipids, and peak-stimulated GH in premenopausal women with obesity. Design and Setting: We conducted a cross-sectional study at a clinical translational research center. Patients: Patients included 21 premenopausal women with obesity (mean body mass index, 34.0 ± 4.5 kg/m(2)) and 17 normal-weight controls (mean body mass index, 21.9 ± 2.0 kg/m(2)) of comparable mean age. Main Outcomes Measures: IMCL and intrahepatic lipids were measured with proton magnetic resonance spectroscopy ((1)H-MRS). Body composition was measured with magnetic resonance imaging. Peak GH was measured after stimulation with GHRH-arginine. Results: Obese subjects had higher IMCL, intrahepatic lipids, abdominal and thigh fat, and thigh muscle mass compared with normal-weight controls. There were strong inverse associations between peak GH and both IMCL and intrahepatic lipids independent of age and visceral adiposity. There were positive associations between IMCL and intrahepatic lipids with measures of insulin resistance and serum triglycerides. Conclusion: In premenopausal women with obesity, peak GH is inversely associated with IMCL and intrahepatic lipids independent of age and visceral adiposity. This suggests that low GH may contribute to insulin resistance in obesity through effects on muscle and intrahepatic lipids.